2019
DOI: 10.2478/pjph-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary preferences and health status of tobacco smokers in Poland

Abstract: The dietary preferences can enhance or reduce negative consequences of tobacco smoking. Thus, the smoking behavior and dietary habits of 99 patients treated against pulmonary, cardiological and gastroenterological diseases in specialist outpatient clinics in Rzeszów were analyzed. The survey questionnaire examined the relation between tobacco smoking and dietary preferences (quantity and regularity of food intake, and frequency of consumption of several foodstuffs) as well as health effects of smoking. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…We found that smokers tended to have a lower habit of VC consumption of 1-4 portions per day (p<0.05), while there were no effects of smoking in all of the categories in FC consumption patterns. This result is in agreement with that of a study of 99 outpatients in Poland 29 and a study with 1,000 smoker respondents, which shows that the higher the fruit and vegetable consumption, the lower the cigarette consumption 30 . In both this study and the previous study, there is an inverse relationship between cigarette consumption and vegetable consumption.…”
Section: Resultssupporting
confidence: 92%
“…We found that smokers tended to have a lower habit of VC consumption of 1-4 portions per day (p<0.05), while there were no effects of smoking in all of the categories in FC consumption patterns. This result is in agreement with that of a study of 99 outpatients in Poland 29 and a study with 1,000 smoker respondents, which shows that the higher the fruit and vegetable consumption, the lower the cigarette consumption 30 . In both this study and the previous study, there is an inverse relationship between cigarette consumption and vegetable consumption.…”
Section: Resultssupporting
confidence: 92%